Axillary skin excision as a treatment for axillary hyperhidrosis. Issue 537 (July 1970) - Weaver, P. C.
Abstract : This report describes three severe cases of axillary hyperhidrosis successfully treated with the Hurley-Shelley operation. It appears to be a simple and effective method of dealing with a condition which is certainly not rare and in its most severe form can be a great social embarrassment to the patient.